15th Aerodynamic Decelerator Systems Technology Conference 1999
DOI: 10.2514/6.1999-1742
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Guided Airdrop System (AGAS)

Abstract: This paper presents an overview of the Affordable Guided Airdrop System (AGAS). AGAS is a low cost, high aititude, deployable airdrop system that will be autonomously controlled via an onboard Guidance, Navigation & Control System (GN&C). The AGAS consists of a round parachute that is controlled via four pneumatic muscle actuators (PMAs) which are connected between the system's payload and risers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The rate of change of position in an inertial reference frame is the transformation of body referenced velocity as (1) where -inertial position vector (down range, cross range and altitude) -body to inertial transformation matrix -body referenced relative velocity vector…”
Section: Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of change of position in an inertial reference frame is the transformation of body referenced velocity as (1) where -inertial position vector (down range, cross range and altitude) -body to inertial transformation matrix -body referenced relative velocity vector…”
Section: Positionmentioning
confidence: 99%
“…Ongoing research and development, with recent flight tests of an Affordable Guided Airdrop System (AGAS), have shown that a parachute's trajectory can be controlled with contracting Pneumatic Muscle Actuators 1 . Earlier development and demonstrations of Precision Guided Airdrop System (PGAS) for a ram-air parafoil incorporated an Inertial Navigation System aided with the Global Positioning System (INS/GPS) to provide navigation data for parafoil guidance 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These include (1) a soft-landing airdrop system, and (2) a low cost steerable airdrop system [6,7]. In general, the relationship between PMA internal pressure, length, and force is nonlinear.…”
Section: • An Accurate and Efficient Element Was Developed For Modelimentioning
confidence: 99%
“…To date, the study of such phenomena has been extremely limited. The CSD model developed under this project provides an effective tool to study this complex problem New soft landing airdrop systems that utilize PMAs as a retraction device have recently been developed and are currently being evaluated [6]. In these systems, a PMA is attached between the confluence point and payload, as shown in Figure A3.…”
Section: Simulation Of Contact During Inflation Of a Round Canopymentioning
confidence: 99%
“…The resultant body-axis error P b is then used to identify which control input must be activated as shown in Eq. (2).…”
Section: Control Systemmentioning
confidence: 99%